Language and Cognitive Behavioural Therapy Practice Paper-Literature Review and Case Example - Satwant Singh (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
This paper addresses the impact of language on cognitive behavioural therapy. Language is emotive and studies carried out in the linguistic field have shown second language is less emotive when describing events occuring in the first language. This paper has been written based on the experiences of a cognitive behavior therapy (CBT) service providing therapy to patients from a diverse cultural and ethnic population. Patients whose first language is not English often receive therapy in their second language. Global migration is a common phenomenon and mainly occurs for economic reasons or threat of violence. This paper has been drawn from the results of a literature review on first and second languages and therapy. Despite being an area that is extremely relevant to therapy, there is an apparent lack of literature in relation to cognitive behavioural therapy for depression and other disorders. CBT is one of the recommended therapies by National Institute of Health and Clinical Excellence (NICE) for the treatment of depression and anxiety disorders. Findings from the linguistic field highlight the potential short comings providing therapy in a patient’s second language. The aim of this paper is to highlight the importance that therapists working in this field have an understanding of how first and second languages function and the role they play in maintaining patients’ psychological problems. This practice paper discusses measures that can be used in cognitive behavioural therapy to deal with this using a case example.